Fischler fait le bilan des résultats du sommet de l'UE sur l'agriculture - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Le Commissaire à l'agriculture Franz...